Analisa Strategi Manajemen Operasional pada Perusahaan Manufaktur PT. Venturindo Jaya Batam - Fendy Cuandra; Chyntia Huang; Kevin Tjoa; Hendri Wijaya; Jery Tango; Lilis Cinthya (Jurnal Mirai Management, 2023)
Operations management is an important process in solving problems that occur in factory companies because they are always faced with unequal environmental conditions. One of the companies that apply management is PT. Venturindo Jaya Batam or PT. VJB founded by Dr. Lim Li Hui Hong in 1993 and engaged in Electronic Manufacturing Services (EMS) located at SM Business Center Block B, Jalan Yos Sudarso, Batu Ampar, Batam. PT. VJB was originally known as PT. JM which was registered in Batam and then in 1998 decided to change the name and establish PT. VJB registered in Jakarta. The purpose of this study is to determine the operational management strategy implemented by PT. Venturindo Jaya Batam. The results of the research show that PT. VJB implements operations management strategy, project management, goods and services design, quality management, process strategy, location strategy, layout strategy, supply chain management, MRP and ERP. In addition, PT. VJB needs to make improvements in its strategy to improve its performance and become more competitive in the market.